Relation between FSH levels and diagnosis of osteopenia vs. osteoporosis in perimenopausal women - Palma Vergara, Lily (2015)
Objectives: To determine the correlation between FSH levels and the decrease in bone mineral density in perimenopausal women. Design: Case-control study. Setting: Hospital Nacional Arzobispo Loayza, Lima, Peru. Patients: Perimenopausal women. Methods: Clinical charts of 114 perimenopausal women attending Gynecology office A Hospital Arzobispo Loayza, during September 2007 through September 2009 were reviewed. Cases consisted in 38 perimenopausal women with osteopenia or osteoporosis and controls by 76 perimenopausal women with normal bone mineral density. Analysis was performed with SPSS v.17 program. Main outcome measures: Correlation of FSH levels and decreased bone density. Results: We found an estimated incidence of 30.7% for osteopenia and 2.6% for osteoporosis. Patients with FSH levels >40 mUI/mL showed 5 times more  risk of developing osteopenia than those with FSH <25 mUI/ mL (OR=5,024, 95%CI 1,9-13,3). Patients with FSH levels 25 to 40 mUI/mL presented 5 times more risk than those with levels <25 mUI/mL (OR=5,024, 95%CI 1,4-17,8). Conclusions: For every 10 mUI/mL FSH increase either osteopenia or osteoporosis risk increased 39 % (OR=1,39,95%CI 1,37-1,42).